Developing a National Financial Inclusion Strategy : The Paraguay Experience - Rawlins, Marlon Rolston; Hwang, Jane C. (World Bank, Washington, DC, 2015)
The FIRST Lessons Learned Series is a collection of FIRST’s technical and functional insights gained from FIRST funded engagements. In this Knowledge Note, based on FIRST’s technical assistance to the Central Bank‘s request to support the development of a National Financial Inclusion Strategy (NFIS), the authors share their Paraguay experience in the development of NFIS. The aim of the Paraguay NFIS was to enhance synergies among multiple initiatives and to have a better sequence of initiatives, set national indicators, develop an action plan and support the start of the NFIS implementation process.